Smart Equipment – A Perspective Paper. Issue 11 (5th September 2018) - Kockmann, Norbert; Bittorf, Lukas; Krieger, Waldemar; Reichmann, Felix; Schmalenberg, Mira; Soboll, Sebastian
Abstract: Chemical equipment has to form a robust and efficient process space and was developed over the last centuries to very sophisticated, often highly specialized devices. With the upcoming information technology new opportunities arise with integrated sensors, and advanced control systems. Smart equipment is designed in form of intelligent modules. Furthermore, adaptive and integrated actuators convert the control signals to directly influence the process, thus, they can be described as responsive equipment. This contribution will give an overview of some activities in this field. Abstract : Smart, responsive equipment for future chemical plants are discussed, e.g., a tubular reactor or crystallizer with integrated sensors, local microcontroller, and self‐adaptive settler.